2018
DOI: 10.3390/nu10121951
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Sarcopenia among Elderly CKD Outpatients on Tertiary Care

Abstract: Background: Sarcopenia is a widespread concern in chronic kidney disease (CKD) as well in elderly patients and is one of the main reasons why low-protein diets for this population are controversial. The aim of this study was to assess the prevalence and correlates of sarcopenia among elderly male patients affected by CKD followed up in an outpatient nephrology clinic, where moderate protein restriction (0.6–0.8 g/Kg/day) is routinely recommended to patients in CKD stage 3b-5 not on dialysis. Methods: This obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 38 publications
2
20
1
5
Order By: Relevance
“…In this regard, our study found a higher prevalence among women across virtually all CKD stages. Other studies in CKD patients have observed variable prevalence rates of sarcopenia: 34.5% (stages 2-3a) and 65.5% (stages 3b-5) [14]; 37% (stages 3-5) [41]; 14% (stages 3-5) greater in men (16%) than in women (8%) and with a significant positive relationship between ASM and GFR [15]; and 12.5% (stages 3b-4 in men aged 60-74) or 55% (stages 3b-4 in men aged > 75) [42].…”
Section: Discussionmentioning
confidence: 95%
“…In this regard, our study found a higher prevalence among women across virtually all CKD stages. Other studies in CKD patients have observed variable prevalence rates of sarcopenia: 34.5% (stages 2-3a) and 65.5% (stages 3b-5) [14]; 37% (stages 3-5) [41]; 14% (stages 3-5) greater in men (16%) than in women (8%) and with a significant positive relationship between ASM and GFR [15]; and 12.5% (stages 3b-4 in men aged 60-74) or 55% (stages 3b-4 in men aged > 75) [42].…”
Section: Discussionmentioning
confidence: 95%
“…Since the CKD population is getting older, ageing is a prominent cause of sarcopenia in ESKD; however, it is likely that this group is more vulnerable to muscle changes than their non-CKD counterparts, but also in comparison to the younger CKD population. This was demonstrated by Çelik et al [51] who noticed that HD patients aged 65 years and older had lower FFM index, serum creatinine and dry body weight than the younger patients (< 65 years) and by D'Alessandro et al [52] who showed that sarcopenia was more prevalent in older (> 75 years) than in younger (65-74 years) seniors with CKD stage 3a and 4 (prevalence 55% vs 12.5%, respectively). Of note, the latter study showed that the three components of sarcopeniaskeletal muscle index, handgrip strength (HGS) and performance tests (sit-to-stand-chair-test and 6-min-walk-test) were significantly lower in the older senior CKD patients [52].…”
Section: Sarcopenia and Ckdmentioning
confidence: 86%
“…This was demonstrated by Çelik et al [51] who noticed that HD patients aged 65 years and older had lower FFM index, serum creatinine and dry body weight than the younger patients (< 65 years) and by D'Alessandro et al [52] who showed that sarcopenia was more prevalent in older (> 75 years) than in younger (65-74 years) seniors with CKD stage 3a and 4 (prevalence 55% vs 12.5%, respectively). Of note, the latter study showed that the three components of sarcopeniaskeletal muscle index, handgrip strength (HGS) and performance tests (sit-to-stand-chair-test and 6-min-walk-test) were significantly lower in the older senior CKD patients [52]. A study based on the EQUAL study (n = 1334) showed that the risk of PEW in CKD patients with eGFR < 20 ml/ In order to minimize influence from fluid retention, special care is advised for dialysis patients when assessing fat free mass.…”
Section: Sarcopenia and Ckdmentioning
confidence: 86%
See 1 more Smart Citation
“…Prevalence of sarcopenia in CKD is high, increases with age and severity of the disease. Several physiopathological models of sarcopenia in CKD have been suggested but protein intake restriction probably plays an important role 20 .…”
Section: Cognitive Impairmentmentioning
confidence: 99%